SOCIO-ENVIRONMENTAL DISCLOSURE AND LEGITIMACY: AN INVESTIGATION OVER THE MAJOR BRAZILIAN BANKS - Prates, Juliana Costa Ribeiro; Rodrigues, Raimundo Nonato; Prates, Thierry Molnar; Cabral, Alexandra Maria Rios (Revista de Contabilidade da UFBA, 2019)
This paper analyzes the connection between sustainability and financial performances of the six biggest banks in Brazil. Brazilian banks were analyzed regarding their socio-environmental and economic disclosure. We collected Socio-environmental data from annual reports, available on banks websites and financial data at Economática® database. Although disclosure data are not audited, which represents a limitation, these banks conduct their business in accordance with sustainable development policies and regulations, and publish information about initiatives. Spearman's non-parametric correlation provided a relationship assessment between variables for each bank. Results in this paper mostly showed a positive correlation between socio-environmental responsibility (SER) and financial performances, even considering the impacts of Brazilian crisis. The objective of this voluntary disclosure lays on companies’ legitimacy as a dialogue mechanism with society.